2007
DOI: 10.1073/pnas.0706901104
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-378 promotes cell survival, tumor growth, and angiogenesis by targeting SuFu and Fus-1 expression

Abstract: MicroRNAs are single-stranded RNA of 18 -24 nt expressed endogenously that play important roles in cancer development. Here, we show that expression of miR-378 enhances cell survival, reduces caspase-3 activity, and promotes tumor growth and angiogenesis. Proteomic analysis indicates reduced expression of suppressor of fused (Sufu), a potential target of miR-378, which was confirmed in vitro and in vivo. Expression of a luciferase construct containing the target site in Sufu was repressed when cotransfected wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
367
2
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 464 publications
(396 citation statements)
references
References 36 publications
25
367
2
2
Order By: Relevance
“…Previously, in carcinoma cell lines U87 and MT-1, as well as in pooled cells, transfection of the 378-pre-miR hairpin was reported to promote tumor growth and angiogenesis. This study showed the miR-378* seed sequence (addressed in this report as miR-378) targets transcription factors SuFu and Fus-1 (22) and promotes cell survival, whereas in our study we observed an apoptosisinducing role of miR-378 in cardiomyocytes. Additionally, miR-378* has been shown to promote a metabolic switch from OXPHOS to glycolysis in the BT-474 breast cancer cell line (20).…”
Section: Discussioncontrasting
confidence: 53%
“…Previously, in carcinoma cell lines U87 and MT-1, as well as in pooled cells, transfection of the 378-pre-miR hairpin was reported to promote tumor growth and angiogenesis. This study showed the miR-378* seed sequence (addressed in this report as miR-378) targets transcription factors SuFu and Fus-1 (22) and promotes cell survival, whereas in our study we observed an apoptosisinducing role of miR-378 in cardiomyocytes. Additionally, miR-378* has been shown to promote a metabolic switch from OXPHOS to glycolysis in the BT-474 breast cancer cell line (20).…”
Section: Discussioncontrasting
confidence: 53%
“…Of the 55 putative targets, we found that only eight have been empirically validated: miR-378-SUFU, miR-101- MYCN,, and let-7c-TRIM71 (Lewis et al 2003(Lewis et al , 2005Yekta et al 2004;Lee et al 2007;Lin et al 2007;Mitomo et al 2008). Interestingly, many of the 47 remaining putative targets have known CSR functions: proteolysis (miR-101-UBE2A); molecular chaperones (miR-125b-DNAJB2, miR-424-HSPA4L, miR-424-DNAJB4, miR-125b-TTC7A, miR-452-TTC7A, miR-378-TTC7A, miR-378-HSP90AB1, miR-138-CCT5, miR-138-HSPA4L, miR-376a-HSPA6, miR-let-7c-HSPB2, and miR-196a-HSPH1) (Kojima et al 2004;White et al 2005); protein trafficking (miR-125-ZFYVE1); metabolism (miR-382-KYNU, miR-378-KLK4, miR-376a-MAN1C1, miR-let-7c-GALE, and miR-let-7c-RNF20); cell cycle progression (miR-101-MYCN, miR-196a-HOXC8, and miR-196b-HOXC8) (Deraison et al 2007;Kamel et al 2009) (Tables 1 and 2).…”
Section: Resultsmentioning
confidence: 99%
“…This miRNA promotes cell survival, tumor growth and angiogenesis by targeting SUFU gene expression. 18 Our previously published gene expression data 11 showed an increase of SUFU transcript level in 5qÀ syndrome patients. Another putative target of miR-378 is transcription factor ETV6.…”
Section: Discussionmentioning
confidence: 99%